2017
DOI: 10.1016/s2215-0366(17)30408-x
|View full text |Cite
|
Sign up to set email alerts
|

The association between paternal and adolescent depressive symptoms: evidence from two population-based cohorts

Abstract: Department of Children and Youth Affairs and Economic and Social Research Council.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 35 publications
4
47
1
Order By: Relevance
“…For example, child difficulties provoke marital tension in both parents, which in turn adversely impacts their well-being [14]. There is more research, however, on the opposite direction of the relationship, with many studies showing that father's psychological distress is related to child emotional and behavioural problems, even after controlling for many important confounding variables, including maternal psychological distress and socio-economic disadvantage [15][16][17][18][19][20][21][22][23][24][25]. Most of these studies have utilised community samples and longitudinal approaches to evaluate the long-term consequences of paternal distress.…”
Section: Introductionmentioning
confidence: 99%
“…For example, child difficulties provoke marital tension in both parents, which in turn adversely impacts their well-being [14]. There is more research, however, on the opposite direction of the relationship, with many studies showing that father's psychological distress is related to child emotional and behavioural problems, even after controlling for many important confounding variables, including maternal psychological distress and socio-economic disadvantage [15][16][17][18][19][20][21][22][23][24][25]. Most of these studies have utilised community samples and longitudinal approaches to evaluate the long-term consequences of paternal distress.…”
Section: Introductionmentioning
confidence: 99%
“…These included: (1) age, as depression appears to be more common in adolescents as compared to children with epilepsy, 1,11 (2) sex, though sex differences in the general population prevalence of depression appear to be more significant than in the epilepsy population, 1,11 (3) seizure severity, 10,12 and (4) parent's own depressive symptom score, as both maternal and paternal depressive symptoms appear to be associated with increased symptoms of depression in children. 28 We also examined the stability of CDI-S scores over three measurements using univariate analysis of frequencies. T scores greater than 64 were considered 'high', while those below 65 were considered 'low'.…”
Section: Discussionmentioning
confidence: 99%
“…The Avon Longitudinal Study of Parents and Children (ALSPAC) study showed that paternal depression in the postnatal period could adversely affect emotional and behavioral outcomes in children aged 3.5 years and was associated with increased risk of conduct problems in especially boys (Ramchandani et al 2005). Based on two other large longitudinal studies, paternal depressive symptoms during childhood were associated with depressive symptoms in their adolescent offspring, independent of the association between maternal and adolescent depressive symptoms (Lewis et al 2017). There is an association between depression in fathers during the postnatal period and subsequent depression in girls at age 18 years, and conduct problems in childhood seem to be a pathway for risk transmission between paternal depression and subsequent depression in adolescent offspring (Gutierrez-Galve et al 2019).…”
Section: Depressionmentioning
confidence: 99%